Synthesis strategies toward improved ordering of [MnO6] octahedra in tunnel structured 2 × 3 and 2 × 4 MnO2. (1st April 2021) - Andris, Ryan; Ridley, Phillip; Byles, Bryan W.; Cullen, David A.; More, Karren L.; Pomerantseva, Ekaterina
Abstract: Improved homogeneity of tunnel size in Na-stabilized 2 × 3 and 2 × 4 MnO2 structures was achieved by identifying and controlling critical synthesis parameters. 2 × 3 and 2 × 4 MnO2 tunnel manganese oxide nanowires were obtained by hydrothermal treatment of Na-birnessite, a layered manganese oxide that undergoes a layer-to-tunnel transition under high pressure and temperature. Herein, the improved ordering of [MnO6 ] octahedra is revealed via a combined analysis of X-ray diffraction patterns and scanning transmission electron microscopy images. We show that crystallinity of the Na-birnessite precursor and the chemical composition of the system during hydrothermal treatment are crucial for achieving the targeted size of the structural tunnels with adequate uniformity. Graphical abstract: Image, graphical abstract